2003
DOI: 10.3354/meps252105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anti-predatory defenses of Red Sea and Caribbean sponges. I. Chemical defense

Abstract: Among marine invertebrates, sponges produce the largest number and diversity of novel secondary metabolites, some of which are used as defenses against predation. Seventeen abundant Red Sea sponge species were assayed for their ability to deter predation by 2 common Red Sea generalist predators: the fish Thalassoma klunzingeri and the sea urchin Diadema setosum. In addition, 17 common Caribbean sponge species were tested against both the Caribbean wrasse T. bifasciatum and the Red Sea wrasse T. klunzingeri. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 63 publications
(61 reference statements)
1
55
1
1
Order By: Relevance
“…The results of this study, together with results in Burns et al (2003), suggest that predation behavior of the 2 wrasse species varies and could be attributed to different mechanisms. Most of the Caribbean reef sponge species examined by Pawlik et al (1995) were found to be chemically defended, whereas less then half of the Red Sea sponges we examined (Burns et al 2003) showed such defense.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The results of this study, together with results in Burns et al (2003), suggest that predation behavior of the 2 wrasse species varies and could be attributed to different mechanisms. Most of the Caribbean reef sponge species examined by Pawlik et al (1995) were found to be chemically defended, whereas less then half of the Red Sea sponges we examined (Burns et al 2003) showed such defense.…”
Section: Discussionmentioning
confidence: 72%
“…Paul 1992, Pawlik 1993, Burns et al 2003. In contrast, the role of sponge structural elements (spicules and spongin fibers) in defense against predation is in doubt (Dayton et al 1974, Pawlik 1983, Meylan 1988.…”
Section: Discussionmentioning
confidence: 99%
“…it has been shown that many of the bioactive compounds have an antipredatory function (e.g. Chanas and Pawlik, 1995;Pawlik et al, 1995;Becerro et al, 2003;Burns et al, 2003). occasionally, although rarely, an allelopathic function has been documented (Porter and Targett, 1988;Turon et al, 1996a;Thacker et al, 1998;engel and Pawlik, 2000).…”
Section: Scientia Marina 73(2)mentioning
confidence: 99%
“…The storage of biologically active secondary metabolites by marine invertebrates is frequently related to their ecological success, in spite of their exposition to predation, infestation by microbial pathogens, overgrowth, fouling and competition for space and nutrients (reviewed in Amsler et al, 2001;Blunt et al, 2007;Faulkner et al, 2004;Lindquist, 2002;Paul, 1992;Pawlik, 1993;Stachowicz, 2001). Marine sponges, ascidians, soft-bodied cnidaria and bryozoans are representative groups of marine invertebrates which are chemically defended against predators (for selected examples, see Aceret et al, 2001;Becerro et al, 1998;Burns et al, 2003;Chanas et al, 1996;Epifanio et al, 1999a;Epifanio et al, 1999b;Kubanek et al, 2002;Lindel et al, 2000;Lindquist, 1996;Marin et al, 1998;McClintock and Baker, 1997;O'Neal and Pawlik, 2002;Pawlik et al, 1995;Pisut and Pawlik, 2002;Stachowicz and Lindquist, 1997;Van Alstyne et al, 1994;Vervoort et al, 1998;Waddell and Pawlik, 2000), fouling (Becerro et al, 1997;Bhosale et al, 2002;Hattori et al, 2001;Henrikson and Pawlik, 1995;Kelly et al, 2003;Wahl et al, 1994), larval settlement (reviewed in Davis et al, 1989;Fusetani, 1997;Martín and Uriz, 1993;Pawlik, 1992) and solar UV radiation (Bandaranayake et...…”
Section: Introductionmentioning
confidence: 99%